PERANCANGAN SISTEM INFORMASI DATA APARATUR SIPIL NEGARA BERDASARAKAN URUTAN KEPANGKATAN BERBASIS WEB DI BAPPEDA KOTA JAMBI - Ediansa, Oka Oka; Yaakub, Saleh; Nugraha, Hafiz (LPPM Universitas Muhammadiyah Jambi, 2022)
At the Bappeda Office (Regional Development Planning Agency) Jambi City has 75 ASN (State Civil Apparatus) employees. So far, in the process of processing employee data, it is still in the conventional way with Microsoft Excel office applications and the data is not yet centralized, it is still scattered in each field, to obtain information or edit employee data, especially the focus of this research is on rank data information which is constantly available. changes, to obtain this information, it must take 2 to 3 days because they have to collect data from their respective fields, then the data is submitted to the Head of the Sub-Division of Personnel and Households, this makes the author think of creating an information system that is realtime and efficient in order to facilitate the performance of a Head of Sub-Division of Personnel and Household. System design is done by using DFD and ERD to model data and processes. With this system, it is hoped that it will make it easier for all ASN employees within the Jambi City Bappeda and related and interested agencies who have access to get the latest information.